Human liver infiltrating γδ T cells are composed of clonally expanded circulating and tissue-resident populations - Hunter, Stuart (J Hepatol, 2018)
BACKGROUND & AIMS: γδ T cells comprise a substantial proportion of tissue-associated lymphocytes. However, our current understanding of human γδ T cells is primarily based on peripheral blood subsets, while the immunobiology of tissue-associated subsets remains largely unclear. Therefore, we aimed to elucidate the T cell receptor (TCR) diversity, immunophenotype and function of γδ T cells in the human liver. METHODS: We characterised the TCR repertoire, immunophenotype and function of human liver infiltrating γδ T cells, by TCR sequencing analysis, flow cytometry, in situ hybridisation and immunohistochemistry. We focussed on the predominant tissue-associated Vδ2(−) γδ subset, which is implicated in liver immunopathology. RESULTS: Intrahepatic Vδ2(−) γδ T cells were highly clonally focussed, with single expanded clonotypes featuring complex, private TCR rearrangements frequently dominating the compartment. Such T cells were predominantly CD27(lo/−) effector lymphocytes, whereas naïve CD27(hi), TCR-diverse populations present in matched blood were generally absent in the liver. Furthermore, while a CD45RA(hi) Vδ2(−) γδ effector subset present in both liver and peripheral blood contained overlapping TCR clonotypes, the liver Vδ2(−) γδ T cell pool also included a phenotypically distinct CD45RA(lo) effector compartment that was enriched for expression of the tissue tropism marker CD69, the hepatic homing chemokine receptors CXCR3 and CXCR6, and liver-restricted TCR clonotypes, suggestive of intrahepatic tissue residency. Liver infiltrating Vδ2(−) γδ cells were capable of polyfunctional cytokine secretion, and unlike peripheral blood subsets, were responsive to both TCR and innate stimuli. CONCLUSION: These findings suggest that the ability of Vδ2(−) γδ T cells to undergo clonotypic expansion and differentiation is crucial in permitting access to solid tissues, such as the liver, which results in functionally distinct peripheral and liver-resident memory γδ T cell subsets. They also highlight the inherent functional plasticity within the Vδ2(−) γδ T cell compartment and provide information that could be used for the design of cellular therapies that suppress liver inflammation or combat liver cancer. LAY SUMMARY: γδ T cells are frequently enriched in many solid tissues, however the immunobiology of such tissue-associated subsets in humans has remained unclear. We show that intrahepatic γδ T cells are enriched for clonally expanded effector T cells, whereas naïve γδ T cells are largely excluded. Moreover, whereas a distinct proportion of circulating T cell clonotypes was present in both the liver tissue and peripheral blood, a functionally and clonotypically distinct population of liver-resident γδ T cells was also evident. Our findings suggest that factors triggering γδ T cell clonal selection and differentiation, such as infection, can drive enrichment of γδ T cells into liver tissue, allowing the development of functionally distinct tissue-restricted memory populations specialised in local hepatic immunosurveillance.